2018
DOI: 10.1155/2018/7159465
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Human Umbilical Cord Mesenchymal Stem Cells at Various Passages on Acute Liver Failure in Rats

Abstract: Recent studies have described beneficial effects of an infusion of mesenchymal stem cells (MSCs) derived from Wharton's jelly tissue, for the treatment of acute liver failure (ALF). However, data on the therapeutic potential of culture-expanded MSCs are lacking. We examined the therapeutic potential of passage five (P5) and ten (P10) human umbilical cord- (hUC-) MSCs via their transplantation into Sprague-Dawley (SD) rats with D-galactosamine (D-GalN) and LPS-induced acute liver failure (ALF). SD rats were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…To date, although BM-MSCs act as the most widely used cells in clinical trials, yet hUC-MSCs possess superiority in large-scale expansion and standardization [31,36]. Of the listed factors, a number of studies indicated that long-term in vitro culture and continuous passages were the prohibiting factor for phenotype and function of MSCs, yet the evidence was still lacking [21,22,31]. Currently, even though we and other investigators have compared the biological signatures of hUC-MSCs with hBM-MSCs or hAD-MSCs in some respects at the cellular level, few of the studies are further focusing on the distinctions at the molecular level [21,37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, although BM-MSCs act as the most widely used cells in clinical trials, yet hUC-MSCs possess superiority in large-scale expansion and standardization [31,36]. Of the listed factors, a number of studies indicated that long-term in vitro culture and continuous passages were the prohibiting factor for phenotype and function of MSCs, yet the evidence was still lacking [21,22,31]. Currently, even though we and other investigators have compared the biological signatures of hUC-MSCs with hBM-MSCs or hAD-MSCs in some respects at the cellular level, few of the studies are further focusing on the distinctions at the molecular level [21,37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we and other investigators found the therapeutic effect of MSCs was closely related to cell viability and homing capacity, which was fundamental for clinical application and regenerative medicine [5,22]. Among the influencing factors, long-term in vitro passages would lead to the reduction of the abovementioned characteristics, together with the changes of biological properties and functions, such as the cytokine secretion, hematopoietic supporting and immunomodulating capacities, and even molecular biological alterations [1,2,9].…”
Section: Huc-mscs At Various Passages Show Similarities In Signaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesenchymal stem/stromal cells (MSCs) are heterogeneous populations capable of multipotential differentiation together with hematopoietic supporting and immunosuppressive properties [9][10][11]. MSCs have been wildly used in preclinical and clinical studies for disease remodeling including acute-on-chronic liver failure, diabetes, Crohn's disease, and acquired AA [9,[12][13][14][15][16]. Generally, as the key component in the microenvironment, MSCs serve as a potential supplementary alternative for refractory AA treatment and have exhibited unexceptionably therapeutic effect mainly through transdifferentiation, immunomodulatory activity, autocrine, and paracrine together with providing an ideal niche [17,18].…”
Section: Introductionmentioning
confidence: 99%